AN INVESTIGATION ON THE EFFECT OF PATERNALIST LEADERSHIP ON JOB SATISFACTION AND EMPLOYEE PERFORMANCE (Third Sector Social Economic Review, 2019)
Leadership styles are known to be effective on employees.  When Turkish culture is considered, it is expected that the paternalist leadership style will affect the job satisfaction and performance of the employees. Therefore, the aim of the study is to reveal the effect of paternalist leadership style on employee's job satisfaction and performance. In this context, a survey study was carried out on 149 research assistants working in universities established after 2006. The data were analyzed with SPSS program. Factor, correlation and regression analyzes were used to analyze the data.  As a result of the study, it was concluded that paternalist leadership style has a significant and positive effect on the job satisfaction and performance of the employee. On the other hand, it has been determined that from the paternalist leadership dimensions, loyalty and satisfaction expectations with the family environment affect internal job satisfaction while the sub-dimension of interest to employees is mostly related to external job satisfaction. Although the loyalty and satisfaction expectancy with the family environment affected the performance significantly and positively, it was found that the sub-dimension of interest did not affect the performance.
Keywords: Paternalist Leadership; Employee Performance; Job Satisfaction; Research Assistant